PEMBERDAYAAN MASYARAKAT MELALUI KEWIRAUSAHAAN PADA INDUSTRI KECIL MENENGAH (IKM) di KALIMANTAN TENGAH SEBAGAI SALAH SATU UNSUR DALAM PERUBAHAN SOSIAL : (Studi Pada Pengembangan Potensi Produk Rotan) - Saputra Adiwijaya; Pipit Anggriati Ningrum (Prodi Sosiologi FISIP UPR, 2018)
Changes in society through entrepreneurship have provided many opportunities for the community to go towards independence or in other words empowering the community. The opening of a society in the global era has placed the study of entrepreneurship as one of its pillars. In the end community empowerment through entrepreneurship provides benefits for community development in a positive direction, this also has a significant impact that the economy of the community through entrepreneurship is better. Government support through Bekraf (Creative Economy Agency) and supported synergistically with the Office of Industry and Trade and other supporting institutions has made entrepreneurship to date as one of the people’s choices in welcoming the global era. This paper tries to provide an analytical point of view that in Central Kalimantan Province the change of society through entrepreneurship by utilizing natural resources in the form of rattan products becomes an important thing in providing its own meaning to the community through the development of a creative economy by not leaving the potential of locality as Dayaks have the motivation to develop in a better direction. But on the side of empowerment in the context of entrepreneurship, especially the development of rattan products also received threats.